Genome Sequencing and Transcriptome Analysis of the Hop Downy Mildew Pathogen Pseudoperonospora humuli Reveal Species-Specific Genes for Molecular Detection. - Rahman, A.; Gongora Castillo, E. L. S. A.; Bowman, M.; Childs, K.; Gent, D. H.; Martin, F. N.; Quesada Ocampo, L. M.
Pseudoperonospora humuli is an obligate oomycete pathogen of hop (Humulus lupulus)that causes downy mildew, an important disease in most production regions in the Northern Hemisphere. The pathogen can cause a systemic infection in hop, overwinter in the root system, and infect propagation material. Substantial yield loss may occur owing to P. humuli infection of strobiles (seed cones), shoots, and cone-bearing branches. Fungicide application and cultural practices are the primary methods to manage hop downy mildew. However, effective, sustainable, and cost-effective management of downy mildew can be improved by developing early detection systems to inform on disease risk and timely fungicide application. However, no species-specific diagnostic assays or genomic resources are available for P. humuli. The genome of the P. humuli OR502AA isolate was partially sequenced using Illumina technology and assembled with ABySS. The assembly had a minimum scaffold length of 500 bp and an N50 (median scaffold length of the assembled genome)of 19.2 kbp. A total number of 18,656 genes were identified using MAKER standard gene predictions. Additionally, transcriptome assemblies were generated using RNA-seq and Trinity for seven additional P. humuli isolates. Bioinformatics analyses of next generation sequencing reads of P. humuli and P. cubensis (a closely related sister species)identified 242 candidate species-specific P. humuli genes that could be used as diagnostic molecular markers. These candidate genes were validated using polymerase chain reaction against a diverse collection of isolates from P. humuli, P. cubensis, and other oomycetes. Overall, four diagnostic markers were found to be uniquely present in P. humuli. These candidate markers identified through comparative genomics can be used for pathogen diagnostics in propagation material, such as rhizomes and vegetative cuttings, or adapted for biosurveillance of airborne sporangia, an important source of inoculum in hop downy mildew epidemics.
Keywords: GENE EXPRESSION PROFILING; GENETICS; HUMULUS; MICROBIOLOGY; OOMYCETES; PATHOGENICITY; PERONOSPORA; PLANT DISEASE